Overview of Nurses' Efforts in Preventing Urinary Tract Infections in Catheterized Patients - Janah, Miftahul; Erwin, Erwin; Karim, Ns. Darwin (Journal of Education Religion Humanities and Multidiciplinary, 2024)
Urinary tract infection (UTI) is a common infection that occurs when bacteria, often from the skin or rectum, enter the urethra and infect the urinary tract. UTI is included in the category of the most common nosocomial infections, with catheterization being the cause of about 80% of all nosocomial infections. This study aims to determine the description of nurses' efforts in preventing urinary tract infections in catheterized patients. This study used a quantitative descriptive design with a simple descriptive approach technique. A sample of 40 people was taken using a purposive sampling technique. Data collection used a standard questionnaire that had been adopted from previous studies. The analysis used was univariate. The results of the univariate analysis showed that the majority of respondents were early adults (26-35 years) as many as 24 respondents (60.0%), as many as 33 respondents (82.5%) were female. The majority of respondents' last education was a Bachelor's degree in Profession as many as 22 respondents (55%), with a length of work of more than or equal to 1 year as many as 40 respondents (100%). The majority of 39 respondents (97.5%) had good efforts in preventing urinary tract infections in catheterized patients. The results of this study showed an assessment of nurses' efforts in preventing UTI from several aspects, namely hand hygiene (100%), use of sterile equipment (100%), perineal hygiene (95%) and SOP (97.5%). The majority of 39 respondents (97.5%) had good efforts in preventing urinary tract infections in catheterized patients, and 1 respondent (2.5%) had sufficient efforts in preventing urinary tract infections.